2022
DOI: 10.3389/fenvs.2022.997865
|View full text |Cite
|
Sign up to set email alerts
|

Executive green investment vision, stakeholders’ green innovation concerns and enterprise green innovation performance

Abstract: During the 14th Five Year Plan period, the green transformation of China’s economic growth mode has become the top priority under the carbon peak and carbon neutrality goal. As an important focus of green transformation and development, manufacturing enterprises need to carry out green innovation to cope with the dual pressure of resource and environmental constraints and supply side structural contradictions. Based on the perspective of business ecosystem theory, this study uses fsQCA method to analyze the A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Based on stakeholder theory, green innovation behavior is not only driven by institutional pressure, but also influenced by other stakeholders such as investors, competitors, consumers, suppliers, and the public (Ilg, 2019; Lin et al, 2014; Qi et al, 2013; Singh et al, 2022; Wan et al, 2022). To meet the environmental requirements of consumers, suppliers, and partners, companies tend to adopt green innovation initiatives to improve their environmental performance (Zhang et al, 2008; Zhang et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on stakeholder theory, green innovation behavior is not only driven by institutional pressure, but also influenced by other stakeholders such as investors, competitors, consumers, suppliers, and the public (Ilg, 2019; Lin et al, 2014; Qi et al, 2013; Singh et al, 2022; Wan et al, 2022). To meet the environmental requirements of consumers, suppliers, and partners, companies tend to adopt green innovation initiatives to improve their environmental performance (Zhang et al, 2008; Zhang et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study of internal influencing factors, Naveed et al [31] took 3736 annual observations of A-share listed companies in China from 2010 to 2019 as samples and found that the gender diversity of the board of directors promotes enterprise green innovation. Wan et al [32] indicated that the management vision and investment vision of enterprise managers are the core supporting factors of green innovation performance. Feng et al [33] built a double-fixed effect model and found that digital transformation significantly improves the green innovation level of enterprises.…”
Section: Research On Enterprise Green Innovationmentioning
confidence: 99%
“…On the contrary, in regards to the depth of internationalization, we propose that the depth of internationalization can have a negative impact on green innovation performance of MNEs for the following reasons: First, green innovation entails the process of efficiency improvement as well as energy conservation (Nie et al, 2022; Vasileiou et al, 2022). Therefore, green innovation needs to integrate information and resources from various fields and markets (Wan et al, 2022). However, the depth of internationalization hinders the opportunities and channels for multinational enterprises to obtain information from multiple overseas markets, which ultimately limits the information obtained and hinders the performance of green innovation.…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%
“…In light of the deteriorating ecological conditions, firms have come to realize that traditional environmental efforts are inadequate to keep up with today's environmental standards. Therefore, an essential solution for them is to carry out green innovation, which means developing new models, systems, and products with the intention of cutting down on resource consumption and reducing ecological damage (Berrone et al, 2013; Wan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%